Improving Seventh Grade Students' Storytelling Skills through Picture Series Media at SMP Negeri 1 Dusun Hilir - Rudiantara Rudiantara; Nurhidayah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This classroom action research investigated how picture-series media improved the learning process and storytelling performance of seventh-grade students at SMP Negeri 1 Dusun Hilir. Fourteen students participated in two cycles, each involving planning, action, observation, and reflection. The researcher collaborated with the Indonesian language teacher. Data were collected through classroom observation, questionnaires, field notes, documentation, and a storytelling performance assessment, and were analyzed descriptively using qualitative and quantitative evidence. Picture-series media were used to scaffold idea generation and narrative sequencing. Reflection after Cycle I led to speaking warm-ups, role-play, intonation practice, teacher modeling, and more contextual picture prompts in Cycle II. The learning process became more active and collaborative, while students demonstrated greater confidence and willingness to perform. Mean storytelling scores increased from 59 in the pre-action stage to 68 in Cycle I and 79 in Cycle II; 93% of the students met the stated achievement criterion by Cycle II. Improvements were also reported in fluency, alignment between story content and the pictures, pronunciation, intonation, and expression. Within this class and research period, picture-series media supported both the learning process and students' storytelling achievement.